Methods for Detecting Fake Profiles in Online Social Networks Using Artificial Neural Networks (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
In light of the current situation, most individuals are participating in online social networks. Everyone, from kids to adults, spends a lot of time on these sites, either learning new things or getting in touch with friends and family in more effective ways. However, today's social media platforms are plagued by a large number of bogus accounts that exploit security flaws in order to steal from the sites or commit cybercrimes themselves.